Outpatient Percutaneous Nephrolithotomy, An Interesting Option: A Systematic Review - BOURGI, Ali; AYOUB, Elias; BRUYERE, Franck (Urology Journal, 2025)
Purpose: The prevalence of kidney stone disease and associated events is rising, with modern surgical approaches emphasizing minimally invasive techniques like ambulatory percutaneous nephrolithotomy (PCNL). This strategy offers potential benefits such as reduced costs, improved efficiency, and high patient satisfaction. However, its safety and feasibility require further evaluation. Methods: A systematic review was conducted following PRISMA guidelines. Databases including PubMed, Embase, Scopus, and the Cochrane Library were searched for studies on ambulatory PCNL published between 1986 and 2024. Out of 2381 identified studies in the initial pool, 17 met the inclusion criteria. Data were analyzed regarding patient selection, technical modifications, surgical outcomes, and complications. Results: The review included 456 patients undergoing 459 procedures. Ambulatory PCNL was feasible for highly selected patients meeting strict criteria (ASA <3, BMI <35 kg/m², no major comorbidities, and minimal stone burden). Mean operative time was 103 minutes, with an average hospital stay of 6.4 hours. The procedure achieved a 93% stone clearance rate, with 15% experiencing mild complications (Clavien-Dindo grade 1-2) and 4.6% readmissions. Severe complications (grade 3-4) were rare (0.4%). Conclusion: Ambulatory PCNL is a safe, efficient option for select patients, optimizing healthcare resources and improving patient outcomes. Wider adoption requires standardized protocols and multicenter studies to expand its application.